The potential of fermentation technology for the process of extracting medicinal plants - Huong, Nguyen Thi Mai; Phong, Bui Thanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Low bioavailability is a standard limitation in medicinal plants. Fermentation has gained attention as a method to enhance the therapeutic potential of active compounds through microbial transformation. Objective: To demonstrate how fermentation improves the efficacy of medicinal plant remedies and their relevance to modern and personalized medicine. Materials and Methods: This review compiles data from studies using microbial strains, such as Lactobacillus, Bacillus, and Aspergillus, with a focus on phytochemical conversions and enhanced bioactivities. This review focused on peer-reviewed research articles, experimental reports, and review papers related to the microbial fermentation of medicinal plants, sourced from scientific databases such as PubMed, ScienceDirect, SpringerLink, and Google Scholar. Selection criteria emphasized studies that examined changes in phytochemical profiles, bioavailability, and biological activities such as antioxidant, anti-inflammatory, and antidiabetic effects after fermentation. Results: Fermentation enhances the antioxidant, anti-inflammatory, and antidiabetic properties of compounds by converting them into more active and bioavailable forms, particularly aglycones. Conclusion: Fermentation presents a promising approach to enhance the efficacy and safety of medicinal plants, thereby supporting the development of personalized therapeutic options.